Synthesis and characterization of powders obtained by complexation of lanthanide ions (Eu3+, Er3+ and Nd3+) with β-diketone and 1,10 – phenanthroline (Research, Society and Development, 2022)
The lanthanide ion complexes have luminescence properties as they provide a wide potential for applications. In this work the Ln(β-dic)3L complexes (where Ln = Eu+3, Er+3 and Nd+3, β-dic = 4,4,4-trifluoro-1-phenyl-1,3-butanedione (HBtfa) and L = 1,10-Phenanthroline (Phen) were synthesized from reaction direct of LnCl3 with β-diketone and the ligand Phen. The reaction lanthanide salts with organic ligands originates or three solid complexes: [Eu(HBtfa)3Phen , Er(HBtfa)3Phen and Nd(HBtfa)3Phen], which differ from the differences of lanthanide salts and ligands, suggesting the occurrence of coordination between lanthanide ions and organic ligands. Thus, the complexes were characterized by solubility test, absorption spectroscopy in the infrared region (FT-IR), X- ray diffraction (XRD). Based on the properties verified, the solubility test was found that the complexes are not chlorine-water and these were quite soluble and acetone. However, the complexes must present good solubility in solution and high stability, photochemical physiological conditions and kinetics under physiological conditions, in addition to not changing their biological structural and chemical properties. Thus, aims at the synthesis and characterization of complex studies of lanthanide ions with β-diketone and 1,10-phenanthroline in the perspective of studying biological applications and drugs with antitumor activities..